Bond Covenants and the Cost of Debt: Evidence from China. Issue 3 (4th March 2017) - Gong, Guangming; Xu, Si; Gong, Xun
ABSTRACT: We examine how the use of covenants in the bond contract affects the cost of debt by using a sample of Chinese firms. We find that (1) the use of financing-related and asset-sale covenants is negatively associated with the cost of debt; (2) the negative relations between financing-related and asset-sale covenants and the cost of debt are more pronounced when a firm's agency conflict is severe or accounting quality is high; (3) the negative relations between financing-related and asset-sale covenants and the cost of debt are significantly intensified if the issuer is a state-owned enterprise (SOE).